Evaluating the performance of traffic flow using SIDRA for roundabouts in Ipoh, Perak - Samikhah Muhammad; Sharinatol Akmanida Jamaludin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Due to rapid development and urbanisation, the traffic systems in Perak are developing and continuously growing in numbers. Evaluation of junction concerning capacity and safety is very important since it is directly related to delay, level of service, accident, operation cost and environmental issues. Traffic congestion happens due to delay and reduction of average speed during AM Peak hours at two roundabouts. This study aims to improve the traffic flow by determining the LOS at two different roundabouts. A traffic study was conducted at “Bulatan Bahagia” and “Bulatan Sultan Iskandar” in Ipoh. Sidra 5.0 application was used as an alternative to Highway Capacity Manual to analyze the junction and LOS performances. This analysis was carried out using SIDRA Software 5.0 to determine the LOS at “Bulatan Bahagia” and “Bulatan Sultan Iskandar” in Ipoh. This study provides recommendations to improve the roundabout performance. The result shows the improvement in the level of service from LOS F to LOS B and from LOS F to LOS D. The percentages of reduction for delay were 2 % and 5% respectively. The finding shows that speed on road has a direct correlation with traffic congestion. The speed improves up to 57 % and 20 %. The analysis indicates that Sidra application utilisation gives the best alternative design for intersections and improve the LOS due to sustainable traffic demand on both upstream and downstream roundabouts.